Growth charts for children-Which ones to use in post Covid era? - Phadke Mrudula; Saunik Sujata; Nair Rajlakshmi; Jotkar Raju; Menon Pramila (International Journal of Nutrition, 2023)
A practical review compares growth chart standards and references for pediatric monitoring after the COVID era. It advises on selection, interpretation, and equity considerations in diverse populations.